Pengaruh CAR, LDR, BOPO dan NPL terhadap ROA dengan Tipe Bank sebagai Variabel Moderasi (Studi pada Bank Umum Konvensional dan Bank Umum Syariah Periode 2019–2023) - Anita Hermawati; Sofia Windiarti (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to analyze the impact of Capital Adequacy Ratio (CAR), Loan to Deposit Ratio (LDR), Operating Expenses to Operating Income (BOPO), and Non-Performing Loans (NPL) on Return on Assets (ROA), while also investigating whether the type of bank (conventional or Islamic) plays a moderating role in these relationships. Employing a quantitative approach, this research utilizes secondary data derived from audited financial statements of commercial banks published on the official website of the Financial Services Authority (OJK) for the 2019–2023 period. The sample, consisting of 85 observations, was determined using G*Power software. Data analysis was performed using panel data regression along with Moderated Regression Analysis (MRA), assisted by EViews version 13. Banks were selected through purposive sampling based on criteria such as completeness of financial reports, consistency of financial ratios, and operational continuity throughout the study period. The empirical findings reveal that CAR has a positive yet statistically insignificant effect on ROA, LDR significantly and positively affects ROA, while both BOPO and NPL have significant negative effects on ROA. Furthermore, bank type moderates the relationships between CAR, BOPO, and NPL with ROA, but does not moderate the effect of LDR. Collectively, the independent variables explain 88.68% of the variation in ROA, with the remaining 11.32% attributed to other factors not captured in the model.